Millennials: America’s cash cow is not necessarily a herd - Steven J. Migacz; James F. Petrick (Journal of Tourism Futures, 2018)
Purpose – The purpose of this paper is to examine the travel motivations, perceived benefits of travel, and the utility of travel mediums among US millennials. Design/methodology/approach – In order to further examine the homogeneity of millennial travelers, millennials were put into two subgroups based on their age and annual income. Data were collected in multiple phases, incorporating both qualitative and quantitative methodological approaches. Findings – Results revealed that several significant differences exist between the proposed millennial subgroups, labeled “young and free millennials” and “professional millennials.” Research limitations/implications – Implications from this study include direction for both tourism marketers and destination suppliers based on the differences and perceptions of both groups and suggest millennials are not a homogeneous market. Originality/value – Millennials are far from being part of a homogenous cohort. Therefore, the current study sought to examine differences in the benefits received from travel and the primary reasons to travel among distinct millennial segments.